Particle alignment reliability in single particle electron cryomicroscopy: a general approach - Vargas, J.; Otón, J.; Marabini, R.; Carazo, J. M.; Sorzano, C. O. S. (Scientific reports, 2016)
Electron Microscopy is reaching new capabilities thanks to the combined effect of new technologies and new image processing methods. However, the reconstruction process is still complex, requiring many steps and elaborated optimization procedures. Therefore, the possibility to reach a wrong structure exists, justifying the need of robust statistical tests. In this work, we present a conceptually simple alignment test, which does not require tilt-pair images, to evaluate the alignment consistency between a set of projection images with respect to a given 3D density map. We test the approach on a number of problems in 3DEM, especially the ranking and evaluation of initial 3D volumes and high resolution 3D maps, where we show its usefulness in providing an objective evaluation for maps that have recently been subject to a strong controversy in the field. Additionally, this alignment statistical test can be linked to the early stages of structure solving of new complexes, streamlining the whole process.